Determinants of adherence to micronutrient powder use among young children in Ethiopia - Samuel, Aregash; Brouwer, Inge D.; Pamungkas, Nindya P.; Terra, Tosca; Lelisa, Azeb; Kebede, Amha; Osendarp, Saskia J. M. (Wiley, 2021)
In Ethiopia, home fortification of complementary foods with micronutrient powders (MNPs) was introduced in 2015 as a new approach to improve micronutrient intakes. The objective of this study was to assess factors associated with intake adherence and drivers for correct MNP use over time to inform scale-up of MNP interventions. Mixed methods including questionnaires, interviews and focus group discussions were used. Participants, 1,185 children (6–11 months), received bimonthly 30 MNP sachets for 8 months, with instruction to consume 15 sachets/month, that is, a sachet every other day and maximum of one sachet per day. Adherence to distribution (if child receives ≥14 sachets/month) and adherence to instruction (if child receives exactly 15[±1] sachets/month) were assessed monthly by counting used sachets. Factors associated with adherence were examined using generalized estimating equations. Adherence fluctuated over time, an average of 58% adherence to distribution and 28% for adherence to instruction. Average MNP consumption was 79% out of the total sachets provided. Factors positively associated with adherence included ease of use (instruction), child liking MNP and support from community (distribution and instruction) and mother's age >25 years (distribution). Distance to health post, knowledge of correct use (OR = 0.74, 95% CI = 0.66–0.81), perceived negative effects (OR = 0.73, 95% CI = 0.54–0.99) and living in Southern Nations, Nationalities and People Region (OR = 0.59, 95% CI = 0.52–0.67) were inversely associated with adherence to distribution. Free MNP provision, trust in the government and field staff played a role in successful implementation. MNP is promising to be scaled-up, by taking into account factors that positively and negatively determine adherence.